2021
DOI: 10.3389/fneur.2021.727089
|View full text |Cite
|
Sign up to set email alerts
|

Age of First Exposure to Contact and Collision Sports and Later in Life Brain Health: A Narrative Review

Abstract: A controversial theory proposes that playing tackle football before the age of 12 causes later in life brain health problems. This theory arose from a small study of 42 retired National Football League (NFL) players, which reported that those who started playing tackle football at a younger age performed worse on selected neuropsychological tests and a word reading test. The authors concluded that these differences were likely due to greater exposure to repetitive neurotrauma during a developmentally sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 141 publications
1
14
0
Order By: Relevance
“…One limitation of our study was that career duration was based on participant's self-reported eAFE to collision sports. This approach, though, is consistent with that of previous eAFE studies investigating similar populations, [11][12][13][14]25 as well as studies of older/retired athletes. 25,44,47,48 We were also unable to verify that individuals participated in collision sports continuously from the age that they self-reported, but as both institutions were sponsored NCAA Division I intercollegiate athletic programs, it is highly likely that this approach is accurate, as lengthy breaks in participation would be quite unusual.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…One limitation of our study was that career duration was based on participant's self-reported eAFE to collision sports. This approach, though, is consistent with that of previous eAFE studies investigating similar populations, [11][12][13][14]25 as well as studies of older/retired athletes. 25,44,47,48 We were also unable to verify that individuals participated in collision sports continuously from the age that they self-reported, but as both institutions were sponsored NCAA Division I intercollegiate athletic programs, it is highly likely that this approach is accurate, as lengthy breaks in participation would be quite unusual.…”
Section: Discussionsupporting
confidence: 89%
“…This approach, though, is consistent with that of previous eAFE studies investigating similar populations, 11-14,25 as well as studies of older/retired athletes. 25,44,47,48 We were also unable to verify that individuals participated in collision sports continuously from the age that they self-reported, but as both institutions were sponsored NCAA Division I intercollegiate athletic programs, it is highly likely that this approach is accurate, as lengthy breaks in participation would be quite unusual. Furthermore, we were unable to account for rule differences across our participants’ collision sport history (eg, a participant may have played hockey for 10 years but was allowed full contact/checking for just 8 of those years), so frequent collisions may not have occurred for the entire career duration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in the present study, there were no significant clinical correlations with CSP. Within the retired players group, there were no significant differences between those with vs. without an abnormal CSP and their lifetime exposure to repetitive neurotrauma, measured by the age of their first exposure to rugby league ( 84 ), total number of years of exposure, number of years of elite (professional) play, or number of lifetime concussions. Moreover, there were no significant differences between retired players with vs. without a CSP on measures of depression, impulsivity, perceived cognitive decline, or on any neuropsychological test.…”
Section: Discussionmentioning
confidence: 86%
“…The authors propose early exposure to RHI reduced CR and protection against "late life neuropathology" (55). This conclusion has been criticized after a large (>3,550) study of NFL players found no correlation between early age at first tackle with subsequent cognitive performance or behavioral problems (56).…”
Section: Is the Vulnerability Of The Brain To The Effects Of Rhi Due ...mentioning
confidence: 99%